O ensino-aprendizado afeto-cognitivo de sujeitos bilíngues em uma atividade de Circle Time - Kemmer, Lígia Gomes Salgueiro (2018)
This research aims to analyze the affective-cognitive teaching-learning approach and its relationship with the concept of agency within the participants in a Circle Time activity in an international bilingual education context. Circle Time, best known in Brazil as Roda de Conversa, is an essential educational practice for children development. Studies have pointed out its importance as a privileged moment for promoting socialization, developing affectivity, building links and constituting critical and creative individuals. On a theoretical basis, the research alludes to the theory of Socio-Historical-Cultural Activity, the concepts of learning, zone of proximal development (ZPD), Perezhivanie, agency, linguistic repertoire, Spinoza’s view of affection, among others. The principles of Circle Time and of elite Bilingual Education have guided this work as well. The project has been conducted as a Critical Collaboration Research – PCCol, in which participants and researchers join in the construction of new possibilities of reality emerging from the research process. The focus of the study was a group of fifth graders of Elementary School in an international school. With permission of the school, data was collected through audio recordings. A survey filled by the students was used in order to analyze the participation of those involved in the Circle Time activity. The responses were then organized in the following levels: contextual-enunciative, discursive and linguistic, as materialized by the lexical choices of the participants. After the categorization of thematic contents, it was possible to notice the development of the discursive dynamics in which the affective-cognitive teaching-learning process and the agency of the participants are based. The results reveal that students have learned aspects regarding living together, dealing with their feelings and asking colleagues for help, displaying especially a relational agency